Maternal Death Review Through the Maternal Perinatal Death Notification Surveillance System: An Aggregate Analysis at Universitas Airlangga Hospital, Surabaya, East Java, Indonesia - Muhammad Ardian Cahya Laksana; Nurani Zulfa Zakiya; Nur Sahila; Ayu Dyah Primaningrum; Asti Alya Rahmahdia; Dinda Zhafira (Masters Program in Public Health, 2026)
Background: Maternal mortality remains a major concern in Indonesia, particularly in referral hospitals that manage high-risk pregnancies. This study aimed to examine maternal deaths and assess contributory factors at Universitas Airlangga Hospital in 2024 using the maternal perinatal death notification (MPDN) system. Subjects and Method: A retrospective-descriptive study was conducted, including all maternal deaths recorded from January to December 2024. Quantitative data were analyzed descriptively, and factors contributing to maternal mortality were classified using the Three Delays Model. A mixed method with multidisciplinary hospital staff provided qualitative insights into clinical and institutional gaps. Results: A total of 11 maternal deaths occurred during the study period, resulting in an MMR of 557 per 100,000 live births. Most deaths occurred in women over 35 years (81.8%) and during the third trimester (81.8%). Non-obstetric complications were the leading cause (40%), followed by pregnancy-related infections (20%) and hypertensive disorders (10%). First, delay factors, particularly socio-cultural barriers, were present in 36.4% of cases, while third, delay factors, including delayed diagnosis and treatment, were identified in 45.5%. FGDs highlighted gaps in emergency preparedness, blood availability, and interprofessional communication. Conclusion: These findings highlight the combined role of clinical complexity and systemic delays, emphasizing the need to strengthen referral readiness, rapid multidisciplinary response, and decision-making to reduce preventable maternal deaths.